Massive open online course in halal food - Shukri, Radhiah; Karim, Roselina; Abdul Rahman, Russly; Mohd Adzahan, Noranizan; Meor Hussin, Anis Shobirin; Baharin, Badlishah Sham; Mohammad Rashedi, Ismail Fitry; Mustapha, Nor Afizah (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Massive Open Online Course (MOOC) is promoted as a good platform to initiate self-learning and is quite useful for blended learning. MOOC in Halal Food was developed to facilitate independency and develop better critical thinking skills of students. The MOOC was designed in an interactive and student-centered environment which includes videos, infographics and assessments.